Design e empreendedorismo: a atuação mutante do designer nos ecossistemas criativos - Serafini, Thaís Pagnussat (Universidade do Vale do Rio dos Sinos, 2016)
The traditional relationships between designers and companies are being transformed by new approaches. They result from factors such as globalization, new information technologies, new consumer trends and the rise of a new industrial panorama. Production, distribution and consumerism systems are also being influenced. In this context, designers are growing less dependent of comissions and more and more requested in complex social problems. If once designing, producing and proposing projects autonomously was not viable, today the new technologies and the creative ecosystems enable these activities. In cases where the rise of a new organization is a consequence of the articulation of a creative network, emerges the designer entrepreneur. If becoming an entrepreneur is a strategy for the young designers, it is necessary to comprehend how the profession transforms within this new scenario. The present work aims to analise the changes in design from the superposition of the design, innovation and entrepreneurship processes. For that, this research has conducted individual interviews with designers entrepreneurs as a way to comprehend their practices. In the results will be presented considerations about the characteristics of the designer entrepreneur and his mutant acting, which is defined by the plurality of design goals, by the superposition of roles and by the horizontal relationships he creates with other actors from the creative ecosystem. Besides, inputs about the changes in the design process will be presented. These are signs of the designer’s acting expansion in order to develop and participate in design processes within the Creative ecosystems for social innovation. Also, it can be prospected that these transformations will impact the instruction of future designers.
Keywords: Designer empreendedor; Atuação mutante; Ecossistemas criativos; Empreendedorismo; Design estratégico; Designer entrepreneur; Mutant acting; Creative ecosystems; Entrepreneurship; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial